2015
DOI: 10.1007/s10549-015-3472-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and behaviour of screen-detected ductal carcinoma in situ of the breast: comparison with symptomatic patients

Abstract: Breast cancer is the most common malignancy in Singapore women. Ductal carcinoma in situ (DCIS) is the putative, non-obligate precursor of the majority of invasive breast cancers. The efficacy of the Singapore breast-screening pilot project in detecting early stage breast cancer led to the launch of a national breast-screening programme, BreastScreen Singapore (BSS), in January 2002. In this study, we compared clinicopathological and immunohistochemical characteristics, as well as clinical outcomes, between sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 52 publications
3
18
2
Order By: Relevance
“…Our results are in line with the study by Koh et al ( n  = 1202 subjects, median follow up 8.2 years), which showed that women with screen-detected DCIS had better overall survival than women with symptomatic DCIS [35]. The high overall survival rates (100% and 97.8% at 10 years, respectively) presented by the authors can be explained by the large proportion (45%) of women aged <50 years at diagnosis in their study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with the study by Koh et al ( n  = 1202 subjects, median follow up 8.2 years), which showed that women with screen-detected DCIS had better overall survival than women with symptomatic DCIS [35]. The high overall survival rates (100% and 97.8% at 10 years, respectively) presented by the authors can be explained by the large proportion (45%) of women aged <50 years at diagnosis in their study.…”
Section: Discussionsupporting
confidence: 93%
“…Symptomatic presentation has been shown to be associated with larger lesion size and higher risk of estrogen receptor negativity [34, 35]. Triple-negative, human epidermal growth factor receptor 2 (HER2), and basal-like phenotypes were found to be more common in symptomatic DCIS, while the luminal A phenotype was more often observed in screen-detected DCIS [35]. Although there was a larger proportion of low-grade DCIS in the screen-detected group in one study, in others there was no difference in distribution by grade [3436].…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic DCIS is more likely to harbour occult invasive disease and to have a poorer overall prognosis than screen‐detected DCIS. In the present study, detection outside screening included asymptomatic DCIS detected by mammography but not within the population‐based screening programme.…”
Section: Discussionmentioning
confidence: 99%
“…Of ten patients who developed distant metastasis without a preceding local recurrence or contralateral breast event, eight had undergone total mastectomy. Symptomatic DCIS is more likely to harbour occult invasive disease and to have a poorer overall prognosis than screen-detected DCIS 21,22 . In the present study, detection outside screening included asymptomatic DCIS detected by mammography but not within the population-based screening programme.…”
Section: Discussionmentioning
confidence: 99%
“…A French study from 2004 showed that DCIS diagnosis via screening was more unusual for the "elderly" (83.6% vs 91.6%, p b .0001), despite that 13.4% of women treated for DCIS was older than 70 years [23]. A number of studies has shown that symptomatic DCIS may be related to a higher invasive recurrence rate and may therefore be associated to worse prognosis, should it recur as invasive disease [24][25][26]. That may have led to the belief that, screening detected, asymptomatic DCIS is clinically much more indolent, but this may not be accurate: In a population-based study from the Netherlands, it was shown that compared with non-screening-related DCIS, women with screen-detected DCIS had a lower risk of developing ipsilateral invasive breast cancer (hazard ratio (HR) = 0.75, 95% CI = 0.59-0.96) and lower all-cause mortality (HR = 0.85, 95% CI = 0.73-0.98), but a similar risk of contralateral invasive breast cancer (HR = 0.86, 95% CI = 0.67-1.10).…”
Section: Dcis Mode Of Detection and Related Outcomesmentioning
confidence: 99%